Arbuscular mycorrhizal symbiosis increases phosphorus uptake and productivity of mixtures of maize varieties compared to monocultures - Wang, Xin‐Xin; Hoffland, Ellis; Feng, Gu; Kuyper, Thomas W.; Cheng, Lei (The Journal of applied ecology, 2020)
Ecological intensification seeks to achieve crop yield increases by intensifying complementary or facilitative interactions between plant species or varieties. Different species of arbuscular mycorrhizal fungi (AMF) exhibit niche differentiation and show selectivity towards certain plants, which can further enhance complementarity. It is not clear whether in the presence of one AMF species, where mycelial networks connect crop species, opportunities for complementarity effects may be reduced. We grew monocultures and mixtures of maize varieties in a greenhouse with one species of AMF, Funneliformis mosseae, during two consecutive years to investigate whether under such conditions the mycorrhizal symbiosis would affect complementarity and overyielding compared to non‐mycorrhizal plants. Variety mixtures showed increased phosphatase activity and mycorrhizal colonization, enhanced phosphorus uptake and overyielding when plants were mycorrhizal. There was no overyielding when plants were non‐mycorrhizal. The increase in relative yield total was due to complementarity effects. Synthesis and applications. Our study implies that appropriate agricultural management that enhances mycorrhizal fungal contribution to ecosystem services may result in overyielding in terms of yield or phosphorus uptake through mixing varieties within one crop species. 摘要 生态集约化旨在通过加强植物物种或品种之间的互补或促进相互作用来实现作物产量的增加。不同种类的丛枝菌根真菌（AMF）表现出生态位分化，对某些植物表现出选择性，从而进一步增强了植物之间的互补性。目前尚不清楚是否存在一种AMF、其菌丝网络可以连接不同作物物种的情况下，产生互补效应的机会可能减少。 我们在温室中连续两年种植了在接种或者不接种Funneliformis mosseae的条件下不同玉米品种单种和混种，以研究在这样的条件下，与非菌根对照相比，AMF是否会影响互补效应和混种产生高产的效应。 当植物为被AMF侵染时，混种处理的磷酸酶活性和菌根侵染率增加，磷和产量也有增加。然而，当植物没有被菌根侵染时，混种是不能产生增产现象的。相对总产量的增加是互补效应的结果。 小结和应用。我们的数据表明，菌根诱导的不同玉米品种混种可以增加产量类似于之前报道的不同植物物种的混种。我们的研究表明，提高菌根真菌对生态系统服务贡献的适当农业管理可能会导致（同一农作物内）不同品种混种产量的提高或磷吸收的增加。 Our study implies that appropriate agricultural management that enhances mycorrhizal fungal contribution to ecosystem services may result in overyielding in terms of yield or phosphorus uptake through mixing varieties within one crop species.